2023
DOI: 10.1111/joor.13494
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and inflammatory mediator levels associated with long‐term prognosis in temporomandibular disorders

Abstract: Temporomandibular disorders (TMD) is a chronic pain disorder that affects 4-60% of the general population and is the second most common cause of pain in the oro-facial region only behind toothache. 1 Generally, TMD is a self-limited disease accompanied by pain of a mild to moderate intensity. However, various comorbidities including headache, sensory disturbances, otologic symptoms, chronic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…25,26 In numerous chronic diseases, these markers are present in elevated concentrations, thereby contributing to the emergence and persistence of chronic pain conditions. 27,28 Pain is a necessary response that serves to protect the body from harm. However, if pain persists beyond the normal healing phase or occurs without injury, it becomes pathological.…”
Section: Sleep Affects the Onset And Progression Of Chronic Painmentioning
confidence: 99%
“…25,26 In numerous chronic diseases, these markers are present in elevated concentrations, thereby contributing to the emergence and persistence of chronic pain conditions. 27,28 Pain is a necessary response that serves to protect the body from harm. However, if pain persists beyond the normal healing phase or occurs without injury, it becomes pathological.…”
Section: Sleep Affects the Onset And Progression Of Chronic Painmentioning
confidence: 99%
“…A prospective study revealed that both short and long sleep durations are substantially associated with an increased risk of depression in adults (16). Other studies support the idea that not enough or too much sleep increases the risk of developing depression (17,18). However, the relationship between sleep duration and depression in menopausal women is unclear.…”
Section: Introductionmentioning
confidence: 99%